Retail Investor Behavior, Fintechs and Sustainable Finance~– Insights from the 6th~European Retail Investment Conference (ERIC) - Hans-Peter Burghof; Nazmie Sabani; Patrick Jaquart (Credit and Capital Markets – Kredit und Kapital, 2021)
The 6th European Retail Investment Conference was hosted by the Stuttgart Stock Exchange from May 12th to 14th, 2021. Due to the persisting global pandemic, this year's conference was held exclusively via online platforms. The conference chairs invited academics and practitioners to participate and discuss empirical and theoretical research focusing on retail investor products and services, new trends in the behavior of private customers, investors' decision-making, investor protection schemes and market microstructure. The keynote about "Climate Finance" was held by Prof. Dr. Zacharias Sautner, Professor of Finance at Frankfurt School of Finance & Management.
Keywords: 330